Analisis Efektivitas dan Efisiensi Anggaran Belanja (Studi Empiris pada Badan Kesatuan Bangsa dan Politik Kabupaten Sleman) - Afuan Fajrian Putra; Novia Dhiniharitsa (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2020)
This research is the result of an internship report which is described to show the facts and explain the nature of the object under study.This research aims to analyze the effectiveness and efficiency of the budget. The object of this research is the National Unity and Politics Agency of Sleman Regency. The results of this research indicate that the level of effectiveness of the expenditure budget into the category is quite effective.While the level of efficiency of the budget shows a very efficient category